Microbudding in mandarin (Citrus reticulata Blanco) as influenced by rootstocks, their age and growing media (IASH Indian Journal of Arid Horticulture, 2026)
This study evaluates the influence of rootstock type, age and growing media on the success of microbudding in Mandarin (Citrus reticulata Blanco). The results indicated that Rough Lemon rootstock at six months of age grown in Cocopeat + Vermicompost (1:1) (R1 G4 A3 ) exhibited the highest microbudding success (79.12%), fastest sprouting (12.98 days), and superior growth parameters, including seedling height (21.35 cm), stock diameter (3.59 mm), and leaf area index (1.17). Additionally, five-month-old Rough Lemon seedlings (R1 G4 A2 ) achieved the highest survival percentage (95.84%), confirming its viability as an alternative treatment. The findings suggest that Cocopeat + Vermicompost (1:1) is an ideal growing medium for maximizing microbudding success and seedling vigor, making it a promising strategy for commercial Mandarin propagation.